A concept design of supercritical CO2 cooled SMR operating at isolated microgrid region. (27th September 2016) - Kim, Seong Gu; Yu, Hwanyeal; Moon, Jangsik; Baik, Seungjoon; Kim, Yonghee; Jeong, Yong Hoon; Lee, Jeong Ik
Summary: Most of the small modular reactor (SMR) concepts developed in the past have compact size and a longer life reactor core than the conventional nuclear power plants. However, these concepts have not achieved the full modularization including power conversion system. This study suggests an innovative concept of a reactor cooled by supercritical state carbon dioxide (S‐CO2 ). A reactor core with uranium carbide fuel controlled by drum type control rods was designed. The core has long life (20 years) without refueling or reshuffling as well as inherent safety features. The reactor can be used as a distributed power source and replace outdated fossil fuel power plants for small cities. Moreover, the authors propose the S‐CO2 Brayton cycle as a power conversion system to achieve compact and lightweight module. Because of compact core and power conversion system, the entire system can be contained in a single module. The target of the system is to be able to transport a single core and power conversion system module via ground transportation. In order to meet this target, single module's total weight is minimized in the order of 100 tons. The external size of a module is less than 7 m in length and 4 m in diameter. It produces 12MWe electricity from 36MWt reactor core. The S‐CO2 Brayton cycle was optimized, and the cycle components such as turbomachineries and heat exchangers were designed preliminarily to observe the potential to maximize the performance while minimizing the weight. Moreover, a dry air‐cooling option to reject waste heat for inland installation was selected for the suggested nuclear system. A concept of passive decay heat removal system was developed, and its performance was examined to determine the required heat removal capacity of the system to assure the system's safety under various anticipated accidents. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Highlights The authors suggest an innovative concept of fast neutron reactor cooled by supercritical carbon dioxide coolant. Entire system can be contained in a single module and be transported by ground way or sea way thanks to the compact core and S‐CO2 power conversion system. The S‐CO2 Brayton cycle with its components were designed to maximize performance while minimizing the weight. Dry type cooling heat exchanger for passive decay heat removal system was designed and analyzed.